A DISTRIBUTION MAP OF CHILDHOOD TUBERCULOSIS IN AGE GROUP OF 0-14 YEARS BY THE COVERAGE OF EXCLUSIVE BREAST MILK AND BCG IMMUNIZATION - Etika Indri Astuty; Lucia Yovita Hendrati (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Tuberculosis (TB) can infect all age groups, even children. Three provinces in Indonesia namely West Java (14%), Papua (13%), and Bangka Belitung provinces (11%) have the highest proportion of children with TB disease. Some previous research reveals that there is a relationship between exclusive breastfeeding and BCG immunization status of children with TB disease. This current study identified the increasing trend of children (aged 0-14 years) with TB disease in Bangka Belitung province based on the coverage of exclusive breastfeeding and BCG immunization. It was observational research with a cross-sectional design. Data were retrieved from seven districts/cities in Bangka Belitung province in 2015-2017. The unit of analysis was the number of overall TB cases, the percentage of BCG immunization coverage, and exclusive breastfeeding. The data were analyzed using the Health Mapper application version 4.3.0.0 with product version 4.03. The number of children (aged 0-14 years) with TB disease increased from 2015-2017, and BCG immunization coverage and exclusive breastfeeding decreased in 2015-2016 only, but swelled in 2016-2017. The number of TB cases was still high despite the high coverage of exclusive breastfeeding and BCG immunization. Several factors such as the quality of vaccines and exclusive breastfeeding might influence the prevalence of TB in children. Future studies should employ more variables to garner more references.